Investigation of the effect of tribological loading parameters on the linear wear rate of a polytetrafluoroethylene-based composite reinforced with polyimide fiber - Yeriomina, Ye. A.; Voloshina, K.R.; Dašić, Predrag (Problems of Tribology, 2026)
The article presents the results of a comprehensive experimental and theoretical study of the tribotechnical characteristics of a composite material based on polytetrafluoroethylene reinforced with polyimide fiber. The main objective of the study was to determine the quantitative regularities governing changes in the intensity of linear wear as a function of external tribological loading parameters, as well as to establish optimal operating modes for the material. A mathematical modeling approach based on a full factorial design was employed to plan and conduct the experiments. The experimental results enabled the derivation of a first-order regression equation describing the dependence of wear on the variable parameters. Statistical analysis of the model included an assessment of its adequacy and the significance of the regression coefficients. By constructing response surfaces, zones of minimum wear intensity were identified, and optimal operating conditions for the material under dry friction were determined. The study confirms the significant influence of both individual factors and their interaction on the wear resistance of the composite material. It was established that deviations of tribological loading parameters from their optimal values lead to a substantial increase in linear wear intensity. The proposed approach can be effectively applied to optimize the operating modes of composite materials based on polytetrafluoroethylene and polyimide fiber in friction units of machines and mechanisms operating under high loads and requiring enhanced wear resistance.